Formation of Environmental Competence of Future Architects by Means of Information and Communication Technologies - Olena Kaidanovska (Pedagogical Discourse, 2025)
In the 21st century, the field of architecture is rapidly evolving, requiring solutions to complex problems closely linked to modern technologies, environmental challenges, and globalization processes. This situation demands that future architects possess not only technical knowledge but also communication, cultural, and environmental skills. The urgent need to address climate change and ecological issues highlights the importance of rethinking educational approaches to equip future architects not only with technical expertise but also with the skills necessary for innovation and sustainable development. The aim of the article is to substantiate the theoretical and methodological principles of forming the environmental competence of future architects based on the use of information and communication technologies (ICT) and to identify effective digital tools that contribute to environmentally oriented professional training. This article focuses on substantiating the theoretical and methodological foundations for developing environmental competence in architecture students through the use of information and communication technologies (ICT). It presents an analysis of contemporary approaches to architectural education, sustainable construction, and the use of digital tools in preparing future architects. The study emphasizes that modern digital tools play a crucial role in fostering environmental competence. The use of BIM, CAD, GIS, software for energy and environmental modeling, VR/AR technologies, digital simulation services, and online collaboration platforms enables comprehensive integration of ecological principles into both design and learning processes. A systematic overview of digital tools with examples of their application in eco-oriented design and education is provided. The findings of the article confirm that integrating ICT into the training of future architects promotes the development of knowledge, skills, and values necessary for designing sustainable and environmentally responsible spaces, preparing competent professionals capable of making responsible environmental impacts.